2012
DOI: 10.1186/1471-2229-12-73
|View full text |Cite
|
Sign up to set email alerts
|

Novel variants of HMW glutenin subunits from Aegilops section Sitopsis species in relation to evolution and wheat breeding

Abstract: BackgroundHigh molecular weight glutenin subunits (HMW-GSs), encoded by the genes at Glu-1 loci in wheat and its related species, are significant in the determination of grain processing quality. However, the diversity and variations of HMW-GSs are relatively low in bread wheat. More interests are now focused on wheat wild relatives in Triticeae. The genus Aegilops represents an important germplasm for novel HWM-GSs and other useful genes for wheat genetic improvement.ResultsSix novel Glu-1 alleles and HMW-GSs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 42 publications
3
28
0
Order By: Relevance
“…Unequal crossover events and slip-mismatching have been suggested as the most likely mechanisms for size variations in HMW-GSs. A detailed comparison of the large HMW-GSs Dx 2.2 and Dx 2.2* as well as Sx 2.9 with Dx 2 have indicated that they have different numbers and lengths of repeatable blocks (Jiang et al 2012;Wan et al 2005). Such duplications most likely arose by unequal crossing over during meiosis (D'Ovidio et al 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unequal crossover events and slip-mismatching have been suggested as the most likely mechanisms for size variations in HMW-GSs. A detailed comparison of the large HMW-GSs Dx 2.2 and Dx 2.2* as well as Sx 2.9 with Dx 2 have indicated that they have different numbers and lengths of repeatable blocks (Jiang et al 2012;Wan et al 2005). Such duplications most likely arose by unequal crossing over during meiosis (D'Ovidio et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…HMW-GSs with large molecular size have attracted considerable research interest. Some of the largest reported HMW-GS genes include Ux from Aegilops umbellulata (Liu et al 2003), Sx from the Sitopsis section of Aegilops (Sun et al 2006;Jiang et al 2012), and the Dx subunits Dx 2.2 and Dx 2.2* from hexaploid wheat (Wan et al 2005). The open reading frames (ORFs) of these genes typically consist of about 3.0 kb in nucleotides and approximately 100-106 kDa in mature protein.…”
Section: Introductionmentioning
confidence: 99%
“…longissima and Ae. sharonensis also corresponded to the Glu1Bx7 of the Chinese Spring (Jiang et al 2012). Ma et al (2013) characterized five novel HMWGS from different accessions of Ae.…”
Section: Sds-page Hmwgs Profile Of Selected Pollen Radiation Hybrids mentioning
confidence: 99%
“…Each Glu-1 locus consists of 2 tightly linked genes encoding an x-type subunit with a larger molecular weight and a y-type subunit with a smaller one, respectively ( Payne 1987 ). Up to now, a lot of studies have been conducted in identifications and function analysis of HMW-GS genes from wheat and its wild relatives ( Anderson and Greene 1989 ; Forde et al 1985 ; Halford et al 1987 ; Jiang et al 2012a ; Jiang et al 2012b ; Jiang et al 2009 ; Liu et al 2003, 2007, 2008, 2010 ; Sugiyama et al 1985 ; Thompson et al 1985 ; Wan et al 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…The grasses of the Triticeae tribe include huge number of wheat and its relatives, which has been widely researched as genetic resource for wheat quality improvement programs. For example, previous reports revealed that wild species has abundant HMW-GS variants which confers to different structural feature and expression level from those of common wheat (Jiang et al 2012a ; Liu et al 2010 ; Wan et al 2002 ; 2005 ).…”
Section: Introductionmentioning
confidence: 99%